Imaging in the investigation and management of Staphylococcus aureus bacteraemia: a role for advanced imaging techniques. Issue 2 (June 2020) - Goodman, A.L.; Cook, G.J.; Goh, V.
SUMMARY: Staphylococcus aureus bacteraemia (SAB) continues to affect ∼25, 000 patients in the UK per year with a high crude mortality of 30% at 90 days. Prompt source control improves outcomes in sepsis and SAB and is included in sepsis guidelines. A recent clinical trial of adjunctive antibiotic treatment in SAB found that the majority of recurrences of SAB were associated with a failure of source management. In this condition, the ability to control the source of infection may be limited by the ability to detect a focus of infection. Echocardiogram is now a routinely used tool to detect such unknown foci in the form of unexpected infectious vegetations. We review the literature to explore the utility of advanced imaging techniques, such as [18F]fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and magnetic resonance imaging (including whole-body MRI), to detect foci which may otherwise be missed. As unknown foci are associated with increased mortality, we propose that increasing the detection of foci could enable improved source control and result in improved outcomes in SAB.